Malawi potato variety catalogue 2021 - Mwenye, O.; Chiipanthenga, M.; Harry, E.; Kapalasa, E.; Kathabwalika, D.; Mvula, T.; Phiri, P.J.; Chinoko, G.; Chitedze, G.; Masamba, Kingsley; Mbewe, W.; Mtonga, A.; et al. (International Potato Center, 2022)
This catalogue is the first for potato varieties registered in Malawi with the Agricultural Technology Clearing Committee (ATCC) of the Department of Agricultural Research Services (DARS) under the Ministry of Agriculture. The catalogue describes potato varieties in terms of use, tuber features, maturity period, yields, and resistance to diseases. A brief description of the growth characteristics has also been provided for each variety. Using the details provided, it is easy to identify each variety to target specific markets. This initiative is aimed at enhancing awareness about the released varieties and helping create the links between seed growers and potato farmers. This catalogue is, therefore, an important reference material for farmers and other market actors.